Customer Satisfaction of BMT Ahmad Dahlan Cawas Mudharabah Deposits: The Role of Service Quality and Product Quality - Choirunnisa, Nadia; Santoso, Fajar (Jurnal Iqtisaduna, 2025)
The study was conducted to determine the influence of service and product quality on customer satisfaction with mudharabah deposits at BMT Ahmad Dahlan Cawas. This type of research is quantitative research with primary data. The data obtained came from questionnaires distributed directly to 91 respondents who were used as samples. The data analysis method used multiple linear regression analysis with the SPSS for Windows 26 application. The study's results showed that service quality partially positively and significantly affected customer satisfaction. Product quality did not have a significant effect on customer satisfaction. The situation in the field showed that separate internal factors made customers use mudharabah deposit products at BMT Ahmad Dahlan Cawas. Service quality and product quality simultaneously affected customer satisfaction.